Determination of Total Phenolic Content of Waru Leaves Methanol and Ethyl Acetate Extracts (Hibiscus tiliaceus L.) - Kusuma Putri, Astrid (Brawijaya University, 2025)
Hibiscus tiliaceus L., also known as the waru plant, is a valuable source of traditional medicine due to its phenolic compounds, which have antibacterial, anti-inflammatory, antithrombotic, anticancer, and antioxidant properties. The study investigates the presence of phenolic compounds in the methanol and ethyl acetate extracts of waru leaf, which were obtained through maceration with methanol and ethyl acetate solvents, highlighting the significant impact of extraction solvent choice on the extract's active compounds. The total phenolic content in the leaf extract of waru (Hibiscus tiliaceus L.) is determined using the Folin-Ciocalteau method, in which the addition of 7% sodium carbonate creates an alkaline atmosphere that produces phenolic ions. Furthermore, it will reduce Folin to form a blue complex. The results showed that the total phenolic content of waru leaf extract (Hibiscus tiliaceus L.) was 15.348 mg GAE/g and 10.060 GAE/g of methanol and ethyl acetate extract, respectively, at a maximum wavelength of 765 nm. The repeatability precision was 1.7 x 10-14% RSD, with the gallic acid standards curve showing good linearity (R2 > 0.999).